A further study on value distribution of the Riemann zeta‐function. Issue 1 (10th November 2017) - Lü, Feng
Abstract: The paper concerns the uniqueness problem of Riemann zeta‐function. It is showed that the Riemann zeta‐function is uniquely determined in terms of the preimages of three complex values a, b, 0 except possibly a set G with n ( r, G ) = o ( r ), where G is called an exceptional set.